Pengaruh Kualitas Pelayanan dan Persepsi Harga Terhadap Minat Beli Pelanggan di Yoehan Busana Cabang Citayam - Rikha Antika Putri; Ratnawaty Marginingsih (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This journal focuses on the Effect of Service Quality and Price Perception on Customer Purchase Interest. The purpose of this study was to determine whether there is an effect of service quality and price perception on customer buying interest. This study uses a quantitative approach method based on statistical data. And the data was collected through a questionnaire distributed to 100 respondents who had made purchases at Yoehan Busana Citayam. The data collection method uses observation and questionnaires with data processing using SPSS version 25, with the data analysis technique used is multiple linear regression analysis, partial significance test (t test), simultaneous significance test (F test), and determination coefficient test (R2 test). The results showed that service quality (X1) and price perceptions (X2) partially (t test) had a positive and significant effect on customer buying interest (Y). then simultaneously service quality and price perceptions affect customer buying interest with a value of Fcount (54.165) > Ftabel (3.09). The results of the coefficient of determination (R2) show that service quality and price perceptions can be explained by the customer purchase interest variable by 52.8%. The remaining 48.2% is explained by other variables not examined.